2019
DOI: 10.1021/acs.jmedchem.9b01572
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Optimization of Coumarin hA3 Adenosine Receptor Antagonists

Abstract: Adenosine receptors participate in many physiological functions. Molecules that may selectively interact with one of the receptors are favorable multifunctional chemical entities to treat or decelerate the evolution of different diseases. 3-Arylcoumarins have already been studied as neuroprotective agents by our group. Here, differently 8-substituted 3-arylcoumarins are complementarily studied as ligands of adenosine receptors, performing radioligand binding assays. Among the synthesized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Based on this theory, another explanation could be that imperatorin targets the adenosine and dopamine systems. Indeed, the structure-based optimization study on synthetic coumarin 3-(4-Bromophenyl)-8-hydroxycoumarin revealed high antagonistic potency and selectivity to the A3 receptor [36]. There are also findings demonstrating that adenosine receptors are colocalized with dopamine receptors, thus influencing their activity [37].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this theory, another explanation could be that imperatorin targets the adenosine and dopamine systems. Indeed, the structure-based optimization study on synthetic coumarin 3-(4-Bromophenyl)-8-hydroxycoumarin revealed high antagonistic potency and selectivity to the A3 receptor [36]. There are also findings demonstrating that adenosine receptors are colocalized with dopamine receptors, thus influencing their activity [37].…”
Section: Discussionmentioning
confidence: 99%
“…None of the studied compounds showed affinity for the A 2B receptor, while quite a few compounds have been found to be nonselective ligands. Various ligands studied proved to be selective to the A 3 receptor, with compound 78 (Figure 23) being the most potent (K i = 258 nM) [164][165][166].…”
Section: Global Pharmacological Effectsmentioning
confidence: 99%
“…They are also well-known inhibitors of urease, 31 acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), 32 cyclooxygenase (COX), 33 lipoxygenase (LOX), 34 monoamine oxidases A and B (MAO-A and MAO-B), 35 tubulin polymerization, 36 carbonic anhydrase, 37 α-glucosidase, 38 inositol-requiring enzyme 1 (IRE-1) RNase, 39 mitochondria-targeting antitumor STAT3, 40 selective cyclin-dependent kinase 9 (CDK9), 41 selective aldehyde dehydrogenase 1A1, 42 coagulation factor XIIa (FXIIa), 43 casein kinase 2 (CK2), 44 steroid sulfatase (STS), 45 chitin synthase (CHS), 46 etc. These heterocyclic scaffolds have antagonistic behavior against chemokine-like factor 1 (CKLF1), 47 G-protein-coupled receptor 35 (GPR35), 48 orphan G-protein-coupled receptor 55 (GPR55), 49 A 3 adenosine receptor, 50 and many others. According to the various and significant biological attributes of the coumarin derivatives, introducing powerful and simple synthetic methods for the preparation of such valuable heterocyclic scaffolds along with respect to green chemistry protocols are undoubtedly precious.…”
Section: Introductionmentioning
confidence: 99%